2018
DOI: 10.1021/acsami.8b03868
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Curcumin Nanoparticles with MMP9-Responsive and Thermos-Sensitive Hydrogel Improves Diabetic Wound Healing

Abstract: Impaired wound healing in diabetics usually leads to life-threatening complications. To develop a system for fastening skin wound healing efficiently and safely in diabetics, thermos-sensitive hydrogel containing the nanodrug, loaded in the form of gelatin microspheres (GMs), was designed to deliver curcumin (Cur) as a therapeutic drug. Cur is a naturally existing polyphenolic compound with a broad range of biological functions useful for potential therapies. Because Cur molecule has weakness in both bioavaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
164
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 208 publications
(176 citation statements)
references
References 50 publications
(66 reference statements)
0
164
0
Order By: Relevance
“…Thus, the nanocurcumin hydrogel improved the wound healing process in diabetic skin of type 1 diabetic rats as compared with normal curcumin hydrogel [201]. In another study, self-assembled curcumin nanoparticles were encapsulated within gelatine microspheres to respond to matrix metalloproteinase 9 (MMP-9) which is commonly over-expressed at diabetic wound sides [202]. Thermosensitive hydrogel in the structure of curcumin-assembled gelatine microspheres was found to improve the capacity of drug release in a sustained manner to the diabetic wound and promoted the efficacy of healing via reducing redox stress and reversing MMP-9-provoked inhibition of cell migration in diabetic mice [202].…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the nanocurcumin hydrogel improved the wound healing process in diabetic skin of type 1 diabetic rats as compared with normal curcumin hydrogel [201]. In another study, self-assembled curcumin nanoparticles were encapsulated within gelatine microspheres to respond to matrix metalloproteinase 9 (MMP-9) which is commonly over-expressed at diabetic wound sides [202]. Thermosensitive hydrogel in the structure of curcumin-assembled gelatine microspheres was found to improve the capacity of drug release in a sustained manner to the diabetic wound and promoted the efficacy of healing via reducing redox stress and reversing MMP-9-provoked inhibition of cell migration in diabetic mice [202].…”
Section: Curcuminmentioning
confidence: 99%
“…In another study, self-assembled curcumin nanoparticles were encapsulated within gelatine microspheres to respond to matrix metalloproteinase 9 (MMP-9) which is commonly over-expressed at diabetic wound sides [202]. Thermosensitive hydrogel in the structure of curcumin-assembled gelatine microspheres was found to improve the capacity of drug release in a sustained manner to the diabetic wound and promoted the efficacy of healing via reducing redox stress and reversing MMP-9-provoked inhibition of cell migration in diabetic mice [202]. Katas and co-researchers formulated a pluronic F-127-based gel containing curcumin-PGT (prostaglandin transporter) DsiRNA chitosan nanoparticles to treat diabetic wounds [203].…”
Section: Curcuminmentioning
confidence: 99%
“…It has also been suggested that wound dressings should enhance leukocyte migration, prevent infection, remove excessive exudates, promote gas exchange, and even provide heat insulation and prevent reinjury . Therefore, functional hydrogels were developed, which were mainly made of materials with good biocompatibility and biodegradability, and were endowed with various functions (such as antioxidative, antimicrobial, anti‐inflammatory, and injectable) . Research shows that multifunctional hydrogels with good biocompatibility are the best choice for biomedical and pharmaceutical applications because they can achieve multistage and multifunctional combination therapy .…”
Section: Causes and Healing Of Woundsmentioning
confidence: 99%
“…Many hydrogels have been reported by successfully loading and delivering curcumin to achieve antioxidant, and the therapeutic effect is remarkable. In a recent study, Wang and co‐workers developed a novel antioxidant hydrogel by loading with curcumin. The results showed that the antioxidant hydrogel could induce drug release in wound bed, and had the ability of antioxidation, which could effectively promote chronic wound healing.…”
Section: Antioxidation Hydrogel In Chronic Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation